ANALISIS PESAN DAKWAH PADA DEPOT NABIL DALAM MENYAMPAIKAN DAKWAH KE MASYARAKAT NAGARI PASIA, KECAMATAN AMPEK ANGKEK, KABUPATEN AGAM - Hisyam Hisyam; Desi Syafriani (ADISAM PUBLISHER, 2024)
Nagari Pasia, situated in the Ampek Angkek Subdistrict of Agam Regency, is one of the regions within Agam Regency that is actively endeavoring to enforce Islamic principles in the form of enjoining what is right and forbidding what is wrong, commonly known as